ANTIINFLAMMATORY OF MAIN COMPOUND FORM PIPER CROCATUM RUIZ AND PAV INHIBITION OF IL-1Β LIPOPOLYSACCHARIDE-INDUCED RAW 264,7 CELLS - LELY, NILDA; WAHYUNI, FATMA SRI; ALDI, YUFRI; ALMAHDY (International Journal of Applied Pharmaceutics, 2022)
Objective: Inflammation is a physiological response to stimuli such as infection and tissue injury that causes an increase in the production of the proinflammatory cytokine IL-1β. Red betel has the potential as an anti-inflammatory drug, the aim study at to determine the anti-inflammatory effect of the main compound of red betel leaves. Methods: Isolation of the main compound from the ethyl acetate fraction of red betel (Piper crocatum) leaves by column chromatography. Cell viability was determined by the MTT method in a concentration range of 1.25; 2.5; 5; 10; 20; 40 ug/ml. The anti-inflammatory effect of the main compound was tested against the inhibition of IL-1β production in LPS-induced RAW 264.7 macrophage cells. IL-1β levels were determined by ELISA. Results: The viability test of the main compound from Piper crocatum leaves showed concentrations that gave viability percentages above 80%, namely 10; 5; 2.5; and 1.25 ug/ml. Concentrations of the main compound Piper crocatum leaves very significantly inhibited the production of IL-1β with p<0.001. Conclusion: The main compound of Piper crocatum leaves has the potential to be used as an anti-inflammatory